Inside Toyland : Working Shopping and Social Inequality. - Williams, Christie (Christine L.) (University of California Press, 2005)
""I got my first job working in a toy store when I was 41 years old."" So begins sociologist Christine Williams's description of her stint as a low-wage worker at two national toy store chains: one upscale shop and one big box outlet. In this provocative, perceptive, and lively book, studded with rich observations from the shop floor, Williams chronicles her experiences as a cashier, salesperson, and stocker and provides broad-ranging, often startling, insights into the social impact of shopping for toys. Taking a new look at what selling and buying for kids are all about, she illuminates the.